2002
DOI: 10.1007/s00424-002-0965-z
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the ryanodine-sensitive Ca 2+ store in GLP-1-induced Ca 2+ oscillations in insulin-secreting HIT cells

Abstract: We investigated intracellular Ca(2+) ([Ca(2+)](i)) oscillations evoked by glucagon-like peptide 1 (GLP-1) in relation to the ryanodine receptor (RyR) and Ca(2+)-induced Ca(2+)release (CICR) mechanism in pancreatic B cell HIT. GLP-1 produced [Ca(2+)](i) oscillations in the cells, both in media with and without Ca(2+), an effect inhibited by ruthenium red and mimicked by 8-Br-cAMPS. In addition, the GLP-1-evoked [Ca(2+)](i) rise was initiated at the local intercellular peripheral cytoplasm, and a resultant expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…These results are along with the findings in the previous studies in rodent cardiomyocytes that GLP-1 or the GLP-1R agonist liraglutide significantly increased intracellular cAMP, which was abolished by the GLP-1R antagonist Exendin (9-39)[13,30]. Also, in the pancreatic β-cell, GLP-1 enhances cytoplasmic Ca 2+ oscillation and insulin secretion via activation of cAMP cascades[22,23]. …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These results are along with the findings in the previous studies in rodent cardiomyocytes that GLP-1 or the GLP-1R agonist liraglutide significantly increased intracellular cAMP, which was abolished by the GLP-1R antagonist Exendin (9-39)[13,30]. Also, in the pancreatic β-cell, GLP-1 enhances cytoplasmic Ca 2+ oscillation and insulin secretion via activation of cAMP cascades[22,23]. …”
Section: Discussionsupporting
confidence: 84%
“…Elevation of intracellular Ca 2+ level can lead to an improvement of myocardial contractility. Several studies in pancreatic β-cells have shown that GLP-1 synchronizes Ca 2+ and cAMP oscillations[10,19,36] and such oscillations involves the ryanodine-sensitive Ca 2+ store[22]. In addition, the experimental evidence has shown that GLP-1 can augment Ca 2+ influx[37,38] and Ba 2+ currents[39] through L-type Ca 2+ channels via the cAMP-dependent PKA pathway in pancreatic β-cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the presence of a ryanodine receptor (RyR) and calciuminduced calcium release (CICR) has been postulated to promote the generation of Ca 2+ waves (Berridge, 2002); the absence of the RyR does not preclude their development (McCarron et al, 2003). Hence, it appears that Ca 2+ oscillations may arise via at least two mechanisms: (1) initiation of the process by IP 3 and perpetuation by CICR from the RyR (Sasaki et al, 2002) and (2) opening and closing of the IP 3 R as a consequence of changes in [Ca 2+ ] i between 100 and 300 nM (Bezprozvanny et al, 1991). When [Ca 2+ ] i is increased modestly , the sensitivity of the IP 3 R is increased, but at higher [Ca 2+ ] i concentrations, the IP 3 R binding site may be inhibited, thereby diminishing Ca 2+ egress from the ER, with a concomitant fall in [Ca 2+ ] i back to baseline levels (McCarron et al, 2003).…”
Section: Ca 2+ Oscillationsmentioning
confidence: 98%
“…In pancreatic ␤-cells, increased cAMP leads to increased activity of voltage-dependent calcium channels (VDCC) (26,37), decreased ATP-sensitive potassium (K ATP ) channel conductance (17,24), and increased activity of inositol 1,4,5-trisphosphate (IP 3 ) receptors in the endoplasmic reticulum contributing to calcium-induced Ca 2ϩ release (7,23,25,35), among other effects. Changes in Ca 2ϩ influx when cAMP levels are elevated can also modulate cAMP dynamics.…”
mentioning
confidence: 99%